3D 프린팅 기술을 활용한 PLA 필라멘트 비탈형 거푸집 연구 - 정준형; 현지훈; 정희상; 고휘재; 이주희; 안요섭; Jeong, Junhyeong; Hyun, Jihun; Jeong, Heesang; Go, Huijae; Lee, Juhee; Ahn, Joseph (한국건설관리학회 논문집, 22(1), 2021)
In recent years, the design of buildings is changing from formal to creative and freeform. Accordingly, the scale of construction technology is changing to architectural design and construction of irregular buildings. Using the FDM method, which is one of the 3D printing technologies, it is possible to manufacture various forms of irregular formwork inexpensively and quickly coMPared to the existing formwork, and it seems to be able to solve the manpower problem. Using a 3D printer, the PLA filament formwork is produced in the form of a cylinder and a rectangular cuboid, and the usability of the PLA filament formwork is confirmed by examining the compression strength test and the degree of deformation and reusability over 28 days of age. Different sizes of additional specimens are also conducted according to the size. As a result of the experiment, it was confirmed that the filament formwork itself has about 3~4MPa strength. As a result of reviewing data through existing linear studies and experiments, it is appropriate to use more than 60% infill, and it is advantageous in terms of strength. As a result of cutting and dismantling the filament formwork, the surface is very clean and there is no damage, so it can be reused. 최근 건축물의 디자인이 정형에서 벗어나서 창의적인 형태를 갖는 비정형 건축물로 변하는 추세이며, 이에 따른 건설기술의 척도가 비정형 건축물의 건축 설계, 시공 등으로 바뀌고 있다. 3D 프린팅 기술 중 하나인 FDM 적층방식을 이용하여 다양한 형태의 비정형 거푸집을 기존 거푸집에 비하여 저렴하고 빠르게 제작할 수 있으며, 인력문제 등을 해소할 수 있을 것으로 보인다. 3D 프린터를 이용하여 PLA 필라멘트 비탈형 거푸집을 원기둥형과 직육면체 형태로 제작하여 재령 28일의 기준을 통한 압축파괴 실험과 변형정도, 재사용성 여부 등을 검토하여 PLA 필라멘트 거푸집에 대한 사용성을 검증하였다. 추가적으로 실험체의 크기를 다르게 하여 크기에 따른 실험도 진행하였다. 실험결과 필라멘트 거푸집 자체가 약3~4MPa의 강도를 갖는 것으로 확인되었으며, 기존 선행연구와 실험을 통한 데이터를 검토한 결과 Infill 60% 이상으로 사용해야 적절하며, 강도적인 측면에서도 유리한 것으로 확인되었다. 필라멘트 거푸집의 절단, 탈형 결과 표면이 매우 깨끗하고 손상이 없어 재사용도 가능할 것으로 기대된다.